Evaluation of haematological variables in patients with typhoid in Pakistan: Hematological Parameters in Patients with Typhoid - Kashif Raza, Syed; Javaid , Hina; Bajwa , Hassan; Saleem, Kamran; Hashim, Muhammad (Pakistan Journal of Health Sciences, 2022)
Typhoid fever results in significant hepatic problems and biochemical abnormalities. The most effective diagnostic procedure now is the bacterial culture, but serologic tests are still often used, and a speedy and accurate diagnostic test for typhoid fever is still required. Objectives: To examine the haematological parameters between typhoid patients and healthy individuals to find any distinctive parameters that could be used as typhoid fever diagnostic indicators. Methods: This study set out to compare haematological changes in 550 patients with 550 healthy persons. Results: We found low hemoglobin (8.95±1.43), low hematocrit (32.62±5.38), high ESR (53.89±9.21), high platelet count (482003±86792), high WBCs count (14464±1694), high neutrophil percentage (63.60±9.26), low lymphocyte percentage (25.33±2.93), and high NLCR (2.498±0.45) against the healthy control group. Conclusions: This distinctive pattern can be easily obtained using a minimally invasive method and used to diagnose typhoid fever.